The Delayed Effect of Picture (Flashcard) on Elementary Students’ Vocabulary Mastery (RETAIN, 2016)
The Delayed Effect of Picture (Flashcard) on Elementary Students’ Vocabulary Mastery Andreana Triwahyuni English Department, Faculty of Languages and Arts, State University of Surabaya andreanatriwahyuni@mhs.unesa.ac.id Ahmad Munir English Department, Faculty of Languages and Arts, State University of Surabaya ahmadmunir@unesa.ac.id Abstrak Penelitian ini bertujuan untuk mengetahui efek langsung (immediate effect) dan tertunda (delayed effect) dari flashcard gambar pada penguasaan vocabulary siswa sekolah dasar, aspek vocabulary makna (meaning), bentuk (form), dan kegunaan (use) yang terbaik dan terburuk yang dapat diingat oleh siswa. Penelitian ini menggunakan pre-eksperimental (one group posttest only design), dengan partisipan yang terdiri dari 30 anak,. Instrumen yang digunakan adalah tes objektif vocabulary yang diujikan tiga kali (immediate test, delayed test 1, dan delayed test 2). Pada immediate effect, peneliti menggunakan SPSS Wilcoxon Signed Rank, pada delayed effect, peneliti mengunnakan Paired sample T-test, sedangkan aspek yang terbaik dan terburuk yang diingat oleh siswa, peneliti menggunakan One-Way ANOVA, serta effect size. Hasil menunjukkan, tidak ada immediate effect serta delayed effect terhadap penguasaan vocabulary siswa. Aspek dari vocabulary yang paling baik diingat oleh siswa adalah aspek form, dan yang paling buruk adalah aspek use, tetapi hal tersebut tak dapat disimpulkan secara utuh karena hasil dari effect size tak selaras dengan One-Way ANOVA. Kesimpulannya, tidak ada efek langsung (immediate effect) maupun tertunda (delayed effect) dari flashcard gambar terhadap penguasaan vocabulary siswa. Aspek dari vocabulary yang paling baik yang dapat diingat oleh siswa adalah aspek bentuk (form) dan yang paling buruk adalah aspek kegunaan (use). Kata Kunci: kosakata bahasa Inggris, flashcard bergambar, efek langsung (immediate effect), efek tertunda (delayed effect), aspek vocabulary. Abstract This study attempts to find out the immediate and delayed effect of picture (flashcard) on the elementary students’ vocabulary mastery, the aspects of vocabulary (meaning, form, and use) that is best maintained and the worst maintained by the students. This study used a pre-experimental design, one group posttests only design, with 30 children as the participants. The instrument that was used in the study was objective vocabulary test that were conducted 3 times which are immediate test, delayed test 1and delayed test 2. To analyze the immediate effect, Wilcoxon Signed Rank was used, while the delayed effect, Paired Sample t-test was used, and to investigate the aspect that is best and worst maintained, One-Way ANOVA and effect size were used. The result found that there is no immediate and delayed effect of pictures on the students’ vocabulary mastery. The aspect of vocabulary that is best maintained is form aspect and the worst maintained is use aspect, however it is inconclusive, since the effect size presents dissimilarly with the result of One-way ANOVA. In conclusion, there is neither immediate effect nor delayed effect of picture (flashcard) on elementary students’ vocabulary mastery. The vocabulary aspect that is best maintained is form, while the worst is use. Keywords: Vocabulary, Picture Flashcards, Immediate Effect, Delayed Effect, Vocabulary Aspects.